2013
DOI: 10.1073/pnas.1219385110
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-92b regulates the development of intermediate cortical progenitors in embryonic mouse brain

Abstract: Cerebral cortical neurons arise from radial glia (direct neurogenesis) or from intermediate progenitors (indirect neurogenesis); intriguingly, the sizes of intermediate progenitor populations and the cortices they generate correlate across species. The generation of intermediate progenitors is regulated by the transcription factor Tbr2, whose expression marks these cells. We investigated how this mechanism might be controlled. We found that acute blockade of mature microRNA biosynthesis in murine cortical prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 31 publications
(48 reference statements)
3
74
0
Order By: Relevance
“…Consistent with neuro-ectodermal priming, derived hIPSC-Ts also expressed higher levels of miRNAs associated with neuronal progenitors (e.g. members of miR-25 family) (Nowakowski et al, 2013). …”
Section: Resultsmentioning
confidence: 92%
“…Consistent with neuro-ectodermal priming, derived hIPSC-Ts also expressed higher levels of miRNAs associated with neuronal progenitors (e.g. members of miR-25 family) (Nowakowski et al, 2013). …”
Section: Resultsmentioning
confidence: 92%
“…Recent research has identified the role of key miRNAs in the developing mouse cortex. For instance, miR-92 maintains proper populations of cortical radial glial cells and intermediate progenitor cells through repression of PTEN and Tbr2 proteins, which in turn modulates subsequent neuronal production (Bian et al, 2013;Nowakowski et al, 2013). Interestingly, miR-92 has been shown to play a key role in maintaining asymmetric self-renewing divisions in the mouse cortex via Tis21 downregulation (Fei et al, 2014).…”
Section: A Novel Regulatory Architecture Within the Primate Germinal mentioning
confidence: 99%
“…MiR92 and miR92b are potential inhibitors of Eomes mRNA translation [73] and are highly expressed in aRG committed to generating BPs [35 ]. Moreover, miR92 restricts the expression of the prodifferentiative gene Tis21 via its 3 0 UTR, thereby ensuring maintenance of asymmetric self-renewing aRG divisions during mouse cortical development, whereas mice lacking the Tis21 3 0 UTR develop a microcephalic neocortex [74].…”
Section: Micrornasmentioning
confidence: 99%